Involvement of the Cohesin Cofactor PDS5 (SPO76) During Meiosis and DNA Repair in Arabidopsis thaliana - Pradillo, Mónica; Knoll, Alexander; Oliver, Cecilia; Varas, Javier; Corredor, Eduardo; Puchta, Holger; Santos, Juan L. (Frontiers in Plant Science, 2015)
Maintenance and precise regulation of sister chromatid cohesion is essential for faithful chromosome segregation during mitosis and meiosis. Cohesin cofactors contribute to cohesin dynamics and interact with cohesin complexes during cell cycle. One of these, PDS5, also known as SPO76, is essential during mitosis and meiosis in several organisms and also plays a role in DNA repair. In yeast, the complex Wapl-Pds5 controls cohesion maintenance and colocalizes with cohesin complexes into chromosomes. In Arabidopsis, AtWAPL proteins are essential during meiosis, however, the role of AtPDS5 remains to be ascertained. Here we have isolated mutants for each of the five AtPDS5 genes (A–E) and obtained, after different crosses between them, double, triple, and even quadruple mutants (Atpds5a Atpds5b Atpds5c Atpds5e). Depletion of AtPDS5 proteins has a weak impact on meiosis, but leads to severe effects on development, fertility, somatic homologous recombination (HR) and DNA repair. Furthermore, this cohesin cofactor could be important for the function of the AtSMC5/AtSMC6 complex. Contrarily to its function in other species, our results suggest that AtPDS5 is dispensable during the meiotic division of Arabidopsis, although it plays an important role in DNA repair by HR.